Status of Lophodermium Needle Blight Disease of Blue Pine (Pinus Wallichiana) in Kashmir (India) - Ahanger, Farooq A.; Dar, G. H.; Beig, M. A.; Sofi, T. A.; Ganie, S. A. (Indian Forester, 2017)
So far no work on status of this disease has been conducted in India. Further, during last few years needlecast in Jammu and Kashmir as a result of Lophodermium infections has severely affected nursery seedlings, pine plantations in forests and those grown for ornamental purpose. The two year studies conducted during 2008 and 2009 revealed that disease was prevalent in all the three surveyed districts of Kashmir viz., Anantnag, Baramulla and Srinagar with disease incidence of 31.1 and 28.8 per cent in nurseries and 42.9 and 35.8 per cent in plantations, respectively. Moderate defoliation of 21 to 30 per cent was noticed in all the surveyed locations of districts Anantnag and Baramulla. However, in Srinagar slight defoliation (<20%) was observed. The blight disease exhibited positive correlation with altitude. The correlation coefficient between altitude and disease incidence on pine plantations and nurseries was 0.33 and 0.30, respectively. The Lophodermium needle blight was observed in all the surveyed locations of the Kashmir valley and requires immediate attention to manage the disease at seedling stage.